PKM E-Commerce Pengrajin UMKM Batik Desa Trusmi - Odi Nurdiawan; Ahmad Faqih; Ade Irma Purnamasari; Salsa Billa Agistina; Nanda Permatasari (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The development of information technology has also changed the views of information technology activists to create breakthroughs in the business sector and promotions to increase competitiveness in developing business. Breakthroughs in the business world, especially the buying and selling business, have led to the use of mobile phones. The use of mobile phones has changed its function to become a multifunctional device for running various kinds of mobile applications, both media for accessing and processing information. Marketplace is an electronic market (virtual market) where the market is a meeting place for buyers and sellers to carry out transactions. Marketplaces are in principle and function the same as traditional markets, only if this marketplace is computerized and connected to the internet. Marketplace or electronic market that brings together sellers and buyers who are connected through electronic transactions that can be accessed quickly, safely, and can be done anywhere and at any time [1] [5] Problems in Community Service The marketing and sales system in craftsmen is still manually, namely the batik craftsman gives the results to the collector (showroom), the showroom or shop owner will resell it at a high price, for example the batik craftsman working on written batik cloth with a Mega Mendung motif is priced at IDR 250,000 by the showroom, then the showroom owner resells the batik cloth at a price a fantastic Rp. 500,000. The urgency of Community Service is how to shorten the distribution of sales of batik craftsmen's products using dodolan application technology. The purpose of the "Dodolan" application is a place for marketing and selling products made by batik craftsmen in Trusmi village, Cirebon district, which is made in the form of an Android-based application. The presence of the Dodolan Application is an effort to realize the attention of batik craftsmen in terms of marketing and sales. In achieving the goal of Community Service, we use the Agile Software Development Cycle with the Extreme Programming (XP) method. The Community Service Stage consists of 5 stages, namely: 1. Meeting Stage, namely brainstorming with users about plans to create a system; 2. Planning stage, namely making Iterations Schedule and Milestones; 3. Design stage, namely making UX-UI Design; 4. Development and Testing stage carried out by the programmer; and 5. Evaluation stage which consists of testing by users, patching by programmers, and project documentation.